The Effect of Green Accounting Implementation and Environmental Performance on Corporate Profitability(A Study on Automotive Sub-sector Manufacturing Companies for the 2020–2023 Period) - Inadhia Amanda; Mariana, Mariana (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the effect of green accounting implementation and environmental performance on the profitability of automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Green accounting and environmental performance are measured through the disclosure of environmental costs in annual reports and the PROPER ratings issued by the Ministry of Environment and Forestry, respectively, while profitability is assessed using Return on Assets (ROA). The research employs a quantitative approach with multiple linear regression analysis. The results indicate that both green accounting and environmental performance have a significant negative impact on company profitability. This suggests that although sustainability practices offer strategic long-term potential, the high implementation costs remain a short-term challenge. These findings imply the need for companies and policymakers to balance environmental commitments with economic efficiency in formulating sustainability strategies.